Reimagining global governance: an Islamic paradigm for justice, peace, and ethical diplomacy - Jalal Nori, Abdulwahed; Lee, Pei May; Tahir, Zhilwan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, Indonesia, 2025)
This article argues that the world needs an alternative framework to international relations (IR) that is more inclusive, just and peaceful. The key principles of Islamic IR provide a comprehensive framework that emphasises justice, cooperation, consultation, and peace, forming a potential basis for global governance and the conduct of ethical diplomacy. It also showcases how Islamic principles challenge the dominant paradigms in IR, reinterprets traditional concepts like Dar al-Islam and Dar al-Harb by framing them within the context of ethical engagement and dialogue, and highlights the similarities between dominant IR theories and Islamic teachings. Finally, this article argues for the establishment of Islamic global governance in these challenging times in order to promote a more peaceful, just and equitable global order.